Process Approach to Regional Labor Market Formation in Post-War Recovery - Miroshnichenko, Tetiana V.; Kozenkov, Dmitro Ye.; Pavlov, D. M.; Sychenko, V. V. (Dnipro University of Technology, Dnipro, 2026)
ENG: To substantiate the applicability of the process approach to the formation and development of the regional labor market under conditions of post-war recovery. Methodology. The research is based on the principles of the process approach and applies methods of theoretical generalization, structural and functional analysis, comparative analysis, and process modeling. An adapted process maturity model developed in accordance with CMM/CMMI logic is used to assess the development level of regional labor market processes. The empirical basis consists of official statistical and analytical data on regional labor market performance in 2025. Findings. The study substantiates the interpretation of the regional labor market as a system of interconnected processes characterized by defined inputs, outputs, participants, and performance indicators. A process maturity model tailored to regional labor markets is proposed and its levels are specified. Based on a pilot assessment, the labor market of Dnipropetrovsk region in 2025 is preliminarily classified at Level 2, with certain elements of Level 3. Originality. The scientific contribution lies in adapting the concept of process maturity to the regional labor market level, developing a framework for assessing process maturity within a socio-economic system, and conceptualizing post-war recovery as a sequence of transitions between maturity levels. Practical value. The proposed approach may be applied by public authorities and regional policymakers to diagnose labor market conditions, identify development priorities, and design evidence-based management decisions during the post-war transformation period.

UKR: Мета. Обґрунтування доцільності застосування процесного підходу до формування й розвитку регіонального ринку праці в умовах повоєнного відновлення. Методика. Дослідження базується на принципах процесного підходу й застосуванні методів теоретичного узагальнення, структурно-функціонального аналізу, порівняльного аналізу та процесного моделювання. Для оцінювання рівня розвитку процесів регіонального ринку праці використана адаптована модель процесної зрілості, сформована на основі логіки CMM/CMMI. Емпіричну основу становлять офіційні статистичні й аналітичні дані щодо функціонування регіонального ринку праці у 2025 році. Результати. У дослідженні обґрунтована можливість інтерпретації регіонального ринку праці як системи взаємопов’язаних процесів із визначеними входами, виходами, учасниками й показниками результативності. Запропонована модель процесної зрілості регіонального ринку праці та визначені її рівні. На основі пілотної оцінки встановлено, що ринок праці Дніпропетровської області у 2025 році відповідає 2 рівню зрілості з окремими ознаками 3 рівня зрілості. Наукова новизна. Полягає в адаптації концепції процесної зрілості до рівня регіонального ринку праці, розробленні моделі оцінювання процесної зрілості соціально-економічної системи та структуризації повоєнного відновлення як послідовності переходів між рівнями зрілості. Практична значимість. Запропонований підхід може бути використаний органами державного й регіонального управління для діагностики стану ринку праці, визначення пріоритетів його розвитку, формування системи показників процесної результативності та прийняття управлінських рішень у період повоєнної трансформації.
Процесний підхід до формування ринку праці регіону у період повоєнного відновлення
T. Miroshnichenko: ORCID 0000-0002-2729-4454; D. Kozenkov: ORCID 0000-0001-5432-0155; D. Pavlov: ORCID 0000-0003-4410-9588; V. Sychenko: ORCID 0000-0001-9655-2317
Keywords: process approach; labor market; process maturity; post-war recovery; regional development; процесний підхід; ринок праці; процесна зрілість; повоєнне відновлення; регіональний розвиток; КМЕУіСГД; SOCIAL SCIENCES; SOCIAL SCIENCES::Business and economics